Clinical symptom tool that raises the index of suspicion for eosinophilic oesophagitis in adults and drives earlier biopsy for definitive diagnosis. Issue 3 (29th November 2016) - von Arnim, U.; Röhl, F.‐W.; Miehlke, S.; Jechorek, D.; Reinhold, D.; Wex, T.; Malfertheiner, P.
Summary: Background: Eosinophilic oesophagitis (EoE) and gastro‐oesophageal reflux disease (GERD) present with overlapping symptomatology and it is challenging to distinguish EoE from GERD clinically before endoscopy. Aim: To investigate the prognostic value of a set of clinical symptoms and laboratory values in patients with EoE and GERD. Methods: In this prospective, single‐centre, observational study, we compared clinical and laboratory data from 202 patients with EoE or GERD (10 relevant characteristics). Those characteristics showing potential significance in a univariate analysis were then included in a multivariate analysis. Results: The set of 10 characteristics (10‐marker set) was able to distinguish between EoE and GERD with good reliability (correct assignment, i.e. agreement with subsequent EGD, of 94.4%). Reduction of the set to the six statistically and clinically most relevant markers continued to give good reliability (88.9%), and further stepwise reduction led to four‐marker sets comprising history of atopy, history of food impaction, proton pump inhibitor refractory symptoms and either immunoglobulin E or peripheral eosinophilia, with correct assignment rates of 91.3% and 85.1% respectively. Conclusions: We have developed a simple and easily applicable clinical/laboratory marker set that helps to distinguish EoE from GERD earlier in the treatment course, thus guiding the endoscopist to perform biopsies from the oesophagus to ensure the diagnosis. The application of the scoring system is expected to diagnose EoE earlier and avoiding delay of adequate treatment. Abstract : Linked Content This article is linked to Chitsaz and Von Arnim and Rohl et al papers. To view these articles visithttps://doi.org/10.1111/apt.13919 andhttps://doi.org/10.1111/apt.13967 .